2011
DOI: 10.1007/s10900-011-9455-6
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Response Rate and Economic Costs Between Mail and Web-Based Surveys Among Practicing Dentists: A Randomized Trial

Abstract: This study explored the economic costs and response rate of mail and web-based surveys with practicing dentists. A random sample of 6,000 practicing dentists was randomly assigned into three groups of 2,000: choice (mail or web-based), postal mail, or web-based. The Florida Tobacco Control Survey 2009, which is composed of 28 questions (including subject demographic questions), served as the survey instrument. A total of 1,232 surveys were returned by the three different groups (21% overall response rate). Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
92
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 16 publications
8
92
4
Order By: Relevance
“…There are several possible reasons for the low response rate overall, including perceived lack of relevance of the survey, the length of the questionnaire, and practical difficulties in accessing the materials online [5,17,18]. Previous research has demonstrated significantly lower levels of participation among health practitioners randomly allocated to online administration of a questionnaire compared with those who were given a pen and paper option [3,19].…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible reasons for the low response rate overall, including perceived lack of relevance of the survey, the length of the questionnaire, and practical difficulties in accessing the materials online [5,17,18]. Previous research has demonstrated significantly lower levels of participation among health practitioners randomly allocated to online administration of a questionnaire compared with those who were given a pen and paper option [3,19].…”
Section: Discussionmentioning
confidence: 99%
“…23 However, gender differences in response rates were not significant when practicing dentists were surveyed. 17 Researchers attempting to increase survey participation by practicing pharmacists and reduce response time and related costs can benefit from examining methodological practices that have been effective in related endeavors. Despite technological developments, achieving high response rates in pharmacist workforce survey research remains a challenge.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…[12][13][14][15][16] It is possible that monetary incentives and/or telephone follow-up may have increased the response rate further, but these options were ruled out on resource grounds. 17,18 The initial August 2015 search identified almost 250 individuals working in direct access practices.…”
Section: Discussionmentioning
confidence: 99%